Clinicopathological Outcome of Early and Late Onset Renal Cell Carcinoma: An Observational Study - Pandit, Durga; Sharma, Uttam Kumar; Chalise, Pawan Raj; Luitel, Bhojraj; Chapagain, Suman; Poudyal, Sujeet; Pradhan, Manish Man; Parajuli, Purushottam; Guragain, Bipin; Gyawali, Milan; et al. (Journal of Institute of Medicine Nepal, 2024)
Introduction Renal cell carcinoma (RCC) is considered a disease of old age and is typically found in the 6th-8th decade of life. The diagnosis of RCC is increasing more rapidly in younger age patients. This study was conducted to evaluate the clinicopathological pattern and outcome of early onset RCC and compare them with the older age group patients. Methods This was a single center observational study. All the patients undergoing radical or partial nephrectomy during the period of November 2019 to October 2022 for renal masses and whose final histopathology report showed RCC were included in the study. Clinicopathological patterns and outcome were compared between the two age groups. Results Among 47 patients, 17 (36.2%) patients were at or below the age of ≤46 years and 30 (63.8%) patients in older age group. There was significant difference in male (29): female (18) ratio between the two age groups (p < 0.005). Younger age patients (≤46 yrs) had higher stage of disease at presentation compared with the older age (>46 yrs) patients [tumor extension into major veins and perinephric tissue (T3) and above 26 vs 21] and they had significantly higher mortality rate (29.4% vs 3.3%, p =0.01). Conclusion Patients aged ≤46 years of age were more frequently affected by RCC with female predominance. Younger age group had higher stage of disease at presentation with higher mortality in comparison to older age group.